Screening for potential prophylactics targeting sporozoite motility through the skin - Ross G. Douglas; Miriam Reinig; Matthew Neale; Friedrich Frischknecht (Malaria Journal, 2018)
Abstract Background Anti-malarial compounds have not yet been identified that target the first obligatory step of infection in humans: the migration of Plasmodium sporozoites in the host dermis. This movement is essential to find and invade a blood vessel in order to be passively transported to the liver. Here, an imaging screening pipeline was established to screen for compounds capable of inhibiting extracellular sporozoites. Methods Sporozoites expressing the green fluorescent protein were isolated from infected Anopheles mosquitoes, incubated with compounds from two libraries (MMV Malaria Box and a FDA-approved library) and imaged. Effects on in vitro motility or morphology were scored. In vivo efficacy of a candidate drug was investigated by treating mice ears with a gel prior to infectious mosquito bites. Motility was analysed by in vivo imaging and the progress of infection was monitored by daily blood smears. Results Several compounds had a pronounced effect on in vitro sporozoite gliding or morphology. Notably, monensin sodium potently affected sporozoite movement while gramicidin S resulted in rounding up of sporozoites. However, pre-treatment of mice with a topical gel containing gramicidin did not reduce sporozoite motility and infection. Conclusions This approach shows that it is possible to screen libraries for inhibitors of sporozoite motility and highlighted the paucity of compounds in currently available libraries that inhibit this initial step of a malaria infection. Screening of diverse libraries is suggested to identify more compounds that could serve as leads in developing ‘skin-based’ malaria prophylactics. Further, strategies need to be developed that will allow compounds to effectively penetrate the dermis and thereby prevent exit of sporozoites from the skin.